2018
DOI: 10.1093/mnras/sty1061
|View full text |Cite
|
Sign up to set email alerts
|

Lyman continuum leakage versus quenching with the James Webb Space Telescope: the spectral signatures of quenched star formation activity in reionization-epoch galaxies

Abstract: In this paper, we study the effects of a recent drop in star formation rate (SFR) on the spectra of epoch of reionization (EoR) galaxies, and the resulting degeneracy with the spectral features produced by extreme Lyman continuum leakage. In order to study these effects in the wavelength range relevant for the upcoming James Webb Space Telescope (JWST), we utilize synthetic spectra of simulated EoR galaxies from cosmological simulations together with synthetic spectra of partially quenched mock galaxies. We fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Clearly this method is complicated in practice, since it requires the determination of the intrinsic UV slope, which depends on the a priori unknown amount of UV attenuation and the attenuation law -especially at high redshift (see e.g. Capak et al 2015;Popping et al 2017;Narayanan et al 2018) -and is sensitive to several parameters including the metallicity, star-formation history, and age (Raiter et al 2010;Binggeli et al 2018). For J1154+2443 we find a UV slope β ∼ −1.9 ± 0.3 from the STIS spectrum, considerably redder than the range of UV slopes predicted by Zackrisson et al (2013), and which is clearly affected by dust attenuation, as shown by Izotov et al (2018a).…”
Section: Strong C Iii] λ1909 Emissionmentioning
confidence: 99%
“…Clearly this method is complicated in practice, since it requires the determination of the intrinsic UV slope, which depends on the a priori unknown amount of UV attenuation and the attenuation law -especially at high redshift (see e.g. Capak et al 2015;Popping et al 2017;Narayanan et al 2018) -and is sensitive to several parameters including the metallicity, star-formation history, and age (Raiter et al 2010;Binggeli et al 2018). For J1154+2443 we find a UV slope β ∼ −1.9 ± 0.3 from the STIS spectrum, considerably redder than the range of UV slopes predicted by Zackrisson et al (2013), and which is clearly affected by dust attenuation, as shown by Izotov et al (2018a).…”
Section: Strong C Iii] λ1909 Emissionmentioning
confidence: 99%
“…Moreover, many local LyC emitters (LCEs) exhibiting high Balmer emission line EWs have been found (Izotov et al 2016b(Izotov et al , 2018a(Izotov et al , 2018b. In any case, Balmer-line EWs are sensitive not only to nebula size but also to starburst age and star formation history (Zackrisson et al 2017;Binggeli et al 2018;Alavi et al 2020). Plagued by such degeneracies, the EW diagnostic may be best when paired with another indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many local LyC emitters (LCEs) exhibiting high Balmer emission line EWs have been found (Izotov et al 2016b(Izotov et al , 2018a. In any case, Balmer line EWs are sensitive not only to nebula size but also starburst age and star formation history (Zackrisson et al 2017;Binggeli et al 2018;Alavi et al 2020). Plagued by such degeneracies, the EW diagnostic may be best when paired with another indicator.…”
Section: Introductionmentioning
confidence: 99%